Optimization of Evaluation Criteria for Energy Research Proposals using the Patton-Sawicki Framework: A Case Study in The Research Organization for Energy and Manufacture - Setyowati, Lia Agustina; Ningrum, Sinta; Nurasa, Heru; Wardani, Lindawati (Journal of Ecohumanism, 2024)
The global energy crisis has affected energy markets and policies around the world. In addition, the issue of global warming requires the world to switch to clean energy sources. The Indonesian government has committed to switching from fossil energy subsidies to renewable energy to achieve Net Zero Emissions (NZE) by 2060 or sooner. The National Research and Innovation Agency (BRIN) established the Energy and Manufacturing Research Organization (OREM) to support the NZE program. One of OREM's initiatives is the Call For Joint Collaboration (CFJC) which provides an opportunity for researchers to propose research proposals in various energy fields. However, the assessment of the CFJC proposal has not used scientific methods or criteria so that the results of the proposal evaluation are not optimal yet. Therefore, this study proposes optimization of evaluation criteria using the Patton-Sawicki Framework to determine the qualified proposal to be accepted. The research uses a qualitative approach method using CFJC proposal data on OREM in 2023. The results show that the proposed method is able to improve the quality of the proposal evaluation process by only accepting proposals that meet the requirements to support the development of NRE sector in Indonesia.